Simulations of Triple-GEM tracker's response for experiments at Jefferson Lab. Issue 11 (2nd December 2019) - Brio, V.; Bellini, V.; Cisbani, E.; Petta, C.; Re, L.; Sutera, C.
ABSTRACT: This paper is about the Gas Electron Multiplier (GEM), a gas detector that will be installed on the new Super BigBite Spectrometer (SBS), under construction at Jefferson Laboratory in Newport News, VA, USA; the main interest of JLAB physics is the study of the fundamental interactions and constituents of hadronic matter and in particular the study of the electromagnetic Form Factors of the nucleons. The Italian group, JLAB12, is engaged in the construction, characterization and commissioning of two of the detectors that will be implemented in SBS: the GEM front tracker and the hadron calorimeter HCAL-J. A Gas Electron Multiplier is a gas detector useful to track the charged particles. It is composed of 2 layers of copper and a layer of Kapton, a dielectric material; all the layers together are inside a box with a mixture of gas: 70 % of Argon an 30 % of CO 2 . In each GEM foil there are a lot of biconical holes, and it is placed between a drift plane and a readout plane; when a charge particle crosses the gas, it loses energy creating couple ion-electron. If we apply a potential difference, the pairs are accelerated by the electric field, and they have enough energy to create an avalanche. The gain that we can reach with a single GEM foil is 1000. In JLAB's configuration for SBS, a TripleGEMs system will be used; a TripleGEM is composed of 3 GEM foil placed in cascade. The advantages of this technology are: the layers structure, so the primary ionization, the multiplication and the charge collection regions are separated, the high gain about 100, 000, the flexibility of geometry, the good spatial resolution about 70 µm, low costs and small streamer or charging up phenomena. To verify GEMs performances and to optimize the digitalization model, we started simulations changing some physical and geometric parameters. In order to run the GEM's simulations, we used two different software: ANSYS Mechanical APDL to create the detector geometry, assign the materials, define the meshes in shape and size and the electric field, and Garfield++, a toolkit for detailed Monte Carlo simulation of a gaseous detector, to evaluate the distribution of the charged particles on the readout plane when we change some parameters like the type of the primary particle, its energy and its incident slope. In particular, we built two different models: a triple GEM model and a cascade model; we are comparing the simulations results with the real test that we did in Juelich (Germany) with a beam of 2.8 GeV protons.